2018
DOI: 10.1186/s40409-018-0161-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of cnidarian extracts from the Caribbean Sea: evaluation of anti-snake venom and antitumor properties

Abstract: BackgroundCnidarians produce toxins, which are composed of different polypeptides that induce pharmacological effects of biotechnological interest, such as antitumor, antiophidic and anti-clotting activities. This study aimed to evaluate toxicological activities and potential as antitumor and antiophidic agents contained in total extracts from five cnidarians: Millepora alcicornis, Stichodactyla helianthus, Plexaura homomalla, Bartholomea annulata and Condylactis gigantea (total and body wall).MethodsThe cnida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Next to no studies have examined the effects of the sea anemone on components of the coagulation cascade to see whether they are able to affect the haemostatic system of prey. Oliveira et al [ 67 ] demonstrated sea anemone extracts from Millepora alcicornis , S. helianthus , Plexaura homomalla , Bartholomea annulata and Condylactis gigantea were able to inhibit haemorrhagic activity induced by Bothrops moojeni venom. Only the C. gigantea (body wall) extracts inhibited thrombin-induced coagulation [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to no studies have examined the effects of the sea anemone on components of the coagulation cascade to see whether they are able to affect the haemostatic system of prey. Oliveira et al [ 67 ] demonstrated sea anemone extracts from Millepora alcicornis , S. helianthus , Plexaura homomalla , Bartholomea annulata and Condylactis gigantea were able to inhibit haemorrhagic activity induced by Bothrops moojeni venom. Only the C. gigantea (body wall) extracts inhibited thrombin-induced coagulation [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al [ 67 ] demonstrated sea anemone extracts from Millepora alcicornis , S. helianthus , Plexaura homomalla , Bartholomea annulata and Condylactis gigantea were able to inhibit haemorrhagic activity induced by Bothrops moojeni venom. Only the C. gigantea (body wall) extracts inhibited thrombin-induced coagulation [ 67 ]. Given the abundance of the haemostatic and haemorrhagic toxins detected in E. quadricolor venom and the abundance of these genes in other sea anemone transcriptomes, it would be useful to investigate haemostatic and haemorrhagic activities of sea anemone venom in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, many approaches have discussed the involvement of PLA 2 s in inflammatory processes [73][74][75]. In addition, PLA 2 s also act on cell membrane metabolism and the production of arachidonic acid, a known precursor of prostaglandins, leukotrienes, and thromboxanes [76][77][78]. Johansson and coworkers demonstrated that incubation of PLA 2 s with rat liver lysosomes resulted in the extravasation of its lysosomal constituents [29].…”
Section: Discussionmentioning
confidence: 99%
“…Since marine bioprospecting began, the world's oceans and their ecosystems have been considered valuable sources to explore for new natural products with a variety of biotechnological applications (Rocha et al, 2011;Merquiol et al, 2019). Although sponges are the foremost providers of marine bioactive compounds, animals belonging to the phylum Cnidaria (such as jellyfish, sea anemones and corals) are also promising reservoirs of compounds with potential drug activity (Oliveira et al, 2018;Merquiol et al, 2019).…”
Section: Introductionmentioning
confidence: 99%